Official guide to the Smithsonian National Museum of Natural History. - Smithsonian Institution (Washington [D.C.] : Smithsonian Books, 1969)
Presents an illustrated guide to the National Museum of Natural History in Washington DC and includes over two hundred color photographs of mammals, fossils, gems and minerals, and ancient cultures of the world.
Welcome to the Museum -- National Museum of Natural History: Where Wonders Never Cease -- The Architecture of Excellence -- Once Upon a Museum -- Building the Collections -- Spencer Fullerton Baird: The Passionate Collector -- Outgrowing the Attic -- Collecting for the Future -- Learning from the Collections -- Why Do We Need So Many Beetles? -- The Museum Today -- The Online Museum -- Behind the Scenes -- Wonders to Come -- For Openers -- The Kenneth E. Behring Family Rotunda -- Constitution Avenue Lobby -- Olmec Colossal Head -- The Janet Annenberg Hooker Hall of Geology, Gems, and Minerals -- The Hope Diamond -- The Harry Winston Gallery -- The National Gem Collection -- Minerals and Gems Gallery -- Mine Gallery -- Rocks Gallery -- Plate Tectonics Gallery -- Moon, Meteorites, and Solar System Gallery -- Fossils: The History of Life -- The Earliest Traces of Life -- Grand Opening: Fossils Galore -- Life in the Ancient Seas -- Conquest of Land -- Reptiles: Masters of Land -- Triceratops -- FossiLab -- Mammals in the Limelight -- Ice Age Mammals -- Biology Halls -- O. Orkin Insect Zoo -- The Smithsonian Butterlly Garden -- Bones -- Two Ocean Giants -- Reptiles and Amphibians -- Birds of the District of Columbia -- Kenneth E. Behring Family Hall of Mammals -- Meet One of Your Oldest Relatives -- Anthropology Halls -- Emergence of Man -- African Voices -- Asian Cultures -- Sikh Heritage Gallery -- Pacific Cultures -- Native Cultures of the Americas -- South America: Continent and Culture -- Origins of Western Cultures.
Keywords: National Museum of Natural History (U.S.) -- Guidebooks; National Museum of Natural History (U.S.); Natural history museums -- Washington (D.C.) -- Guidebooks; Natural history museums; Washington (D.C.); Guidebooks